Effects of Different Agricultural Waste Composts on Cabbage Yield and Rhizosphere Environment - Jue Wang; Bo Zhang; Jie Wang; Guobin Zhang; Zhibin Yue; Linli Hu; Jihua Yu; Zeci Liu (Agronomy, 2024)
The return of agricultural waste to the field is one of the most effective strategies of increasing crop yield, improving the soil’s physicochemical properties, and improving the soil rhizosphere environment. In the present study, sheep manure (SM), cow manure (CM), tail vegetable (TV), mushroom residue (MR), and corn straw (CS) were used as raw materials, and no fertilization (CK1) and local commercial organic fertilizer (CK2) treatments were used as controls. Eight composts were set up using specific mass ratios of different compost materials. After fermentation, field experiments were conducted to determine the cabbage yield, soil’s physicochemical properties, and soil rhizosphere conditions. The eight composts increased the soil organic matter and nutrient contents significantly. Among the eight fermentation formulas, T6 (CM:CS:TV:SM = 1:1:2:6), T7 (MR:CS:TV:SM = 1:1:2:6), and T8 (CM:MR:CS:TV:SM = 1:1:1:2:5) were relatively effective. Therefore, high-throughput sequencing was performed on T6, T7, T8, CK1, and CK2. T6, T7, and T8 exhibited increased relative abundance of Proteobacteria, Actinomycetes, and Firmicutes, while the Acidobacteria abundance was decreased. In addition, Ascomycota’s and Basidiomycetes’ relative abundance decreased, and the oil chytrid and mortierella increased. The microbial community structure was affected significantly by pH, electrical conductivity, available potassium, available nitrogen, and organic matter. In general, the three composts increased yield by improving the soil’s physicochemical properties, fertility, and microbial community structure. Among them, T6 had the most significant effect and is the optimal formula for use as a local organic cabbage fertilizer, and it could facilitate sustainable agricultural development.